Effects of different doses marbofloxacin on biochemical and hematological parameters in sheep - Feray Altan; Orhan Çorum; Duygu Durna Çorum; Kamil Üney (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed to determine the effect of IM marbofloxacin at different doses on biochemical and hematological parameters in healthy sheep. Materials and Methods: The study was carried out on twenty four healthy Akkaraman rams (2-5 years old) randomly selected in four dose groups according to parallel design. There are six animals in each dose group. There are six animals in each dose group. Six animals in each group were injected with marbofloxacin at the dose levels of 2, 4, 6 and 10 mg/kg, respectively, in the semitendinosus muscle. Blood samples were collected using a catheter placed in the left jugular vein at 0 (pre-treatment), and 10. and 22 hours post-dosing. Biochemical parameters, such as, albumin, alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase, cholesterol, triglyceride, total protein, blood urea nitrogen, creatinine, and gamma-glutamyl transferase were determined in autoanalyzer. Hematological parameters, such as white blood cells, red blood cells, hemoglobin, hematocrit, and platelet were measured in blood cell counter. Results: No significant differences in hematological and serum biochemical parameters were found between the groups. Conclusion: These results indicate that the marbofloxacin after a single intramuscular injection up to 10 mg/kg following IM administration in sheep had no significant side effects on the biochemical and hematological parameters measured.